Evolution of Spanish population well-being during the COVID-19 pandemic: Results from the COSMO-Spain study - Catarina Santos-Ribeiro; Carmen Rodríguez-Blázquez; Alba Ayala; María Romay-Barja; María Falcón; Maria João Forjaz (Heliyon)
Introduction: The COVID-19 pandemic affected mental health worldwide. The COSMO-Spain study analyses risk perceptions, behaviours, knowledge and other pandemic related variables, such as well-being. This work aimed to assess the evolution of self-reported well-being in Spain from May 2021 to September 2022 and its association with demographic and COVID-19 related factors. Methods: An online, nationwide cross-sectional panel survey was applied in seven rounds with 1000+ participants each, with a total sample of 7266 participants, representative of the Spanish adult general population. The main variable was well-being, measured with the World Health Organization Well-Being Index (WHO-5) total score, an index with a total score from 0 to 100 (0 = worst well-being, 100 = best well-being). Other variables included in the survey were: sociodemographic data, concern about COVID-19, feelings of depression and fear, COVID-19-related worries, risk perception, self-efficacy, preventive behaviours, pandemic fatigue, health literacy, information search behaviours, and trust in several institutions. A multiple linear regression was run to analyse the associated factors with the WHO-5 total score. Results: The WHO-5 total score showed a significant increase from rounds 6 (May–June 2021) to 8 (September–October 2021). Women (standardized b coefficient (b) = -0.10), youth or people with lower socioeconomic status (worsened financial situation (b = −0.10) or unemployed/furloughs (b = −0.04)) reported lower well-being levels, whereas having a university-level education showed the opposite (b = 0.11). Feeling less depressed was associated with higher well-being (b = 0.31). Conclusions: This study shows rising levels of well-being until a plateau was reached in October 2021. Vulnerable groups may be at higher risk of worsened mental health and should be addressed by policymakers. Further longitudinal studies should evaluate causality and evolution patterns of well-being throughout the COVID-19 pandemic.